THU0439 Incidence and Risk Factors for Fractures in Patients with Rheumatoid Arthritis. (10th June 2014) - Kim, D.; Cho, S.-K.; Choi, C.-B.; Yoo, D.-H.; Lee, H.-S.; Jun, J.-B.; Lee, J.; Lee, S.-S.; Kim, T.-H.; Yoo, W.-H.; Sung, Y.-K.; Bae, S.-C.
Abstract : Background: Patients with rheumatoid arthritis (RA) have an increased risk of fracture caused by loss of joint function, medication and decreased bone mineral density (BMD). Objectives: This study aimed to identify the incidence rate of fractures in RA patients and to explore the possible risk factors for fractures in RA patients. Methods: A total of 3, 557 RA patients in the KORean Observational study Network for Arthritis (KORONA) were included in this study. The information of new fractures was obtained through annual patient self-reported questionnaires. Their demographic profile, disease-specific outcomes, history of prior fracture, medications, and available BMD data were collected. The standardized incidence ratio (SIR) for fractures in RA patients was calculated and possible risk factors for fractures were explored using the logistic regression analysis. To identify the effect of bisphosphonate in RA patients with osteoporosis, we further performed logistic regression analysis. Results: A total of 3, 557 RA patients were included in this study and the 194 patients with 215 fractures were observed over a mean follow-up of 18 months. Vertebral fractures (n=36) were the most common fractures, followed by wrist (n=33) and rib fractures (n=21). Total fracture crude incidence rates were 41, 34.5 and 42.1 per 100, 000 person year for total, male, and female patients, respectively. The SIRs of all types and major osteoporotic fractures were 3.11[95% confidence interval (CI) 2.69-3.53], and 1.41 (CI 1.05-1.86), respectively. Patients who have experienced any fracture had older age (p<0.01), longer disease duration (p=0.02), having osteoporosis (p<0.01), history of prior fracture (p<0.01) and were currently using corticosteroid (p=0.03) and bisphosphonates (p<0.01). Since BMD is most strong predictor for future fracture, logistic regression to identify the risk factors for fractures was performed for patients who had BMD data at baseline (n=866), and only having osteoporosis [Odds ratio (OR) 2.69, CI 1.17-6.18, p=0.02] was independently related to incident fracture in RA patients. In addition, older age (OR 1.03, CI 1.00-1.06, p=0.05) tend to increase the fracture incidence. Subgroup analysis for osteoporosis patients (T score <-2.5, n=210), higher functional disability with HAQ increased fracture risk (OR 2.06, CI 1.07-3.96, p=0.03) and the use of bisphosphonate showed a protective effect for future fracture (OR 0.33, CI 0.13-0.83, p=0.02) in RA patients. Conclusions: Rheumatoid arthritis patients had a 3-fold increased risk of fractures as compared to those of general population. Classical risk factors for fracture such as osteoporosis with BMD and old age were associated with fractures in RA patients. In RA patients with osteoporosis, higher functional disability was a risk factor for fracture, while the use of bisphosphonate showed protective effect on their future fracture. Acknowledgements: This study was supported by a grant of the Korea Healthcare technology R&D Project, Ministry of Health and Welfare, Republic of Korea.(HI10C2020). Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3982